ENHANCING STUDENTS’ WRITING ABILITY THROUGH BLENDED LEARNING AT SMA NEGERI 4 MAKASSAR - ARTIKA SANDA MAIRI PAEWA; St. Haliah Batau; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
This study aimed to determine to enchance the students’ ability in writing narrative text through blended learning of class Xl-5 students of SMAN 4 Makassar in writing narrative texts using the blended learning method. This study used a pre-experimental method. The Subject of this study were students of class Xl-5 at SMAN 4 Makassars emester in the academic year 2022/2023, with a sample of 34 students. Data collection was narrative text through offline and online. The research data collected through the test showed that the student's writing ability after the research was conducted, students were more interested in using the blended learning method in writing narrative texts. Based on the results of the data analysis, it can be seen that the student's results in the offline pre-test were 49.03. Then after getting treatment, the students' pre-test scores increased to 79.47 in the post-test. While the students' results in the online pre-test were 52.18, and after getting treatment, the students' pre-test scoreincreased to 89.15 in the post-test. It can be concluded that students' writing skills are improved in the online learning.So it can be concluded that using the blended learning method can improve students' learning ability in writing narrative texts at SMAN 4 Makassar.